Early Regenerative Response in the Intrathoracic Porcine Esophagus—The Impact of the Inflammation. Issue 6 (4th December 2013) - Jönsson, Linus; Friberg, Lars‐Göran; Gatzinsky, Vladimir; Jennische, Eva; Sandin, Anders; Abrahamsson, Kate
Abstract In order to improve the treatment of children born with long‐gap esophageal atresia, a porcine model was developed for studying esophageal regrowth using a bridging graft composed of a silicone stented Biodesign mesh. The aim of the study was to investigate how leakage and contact between the native muscle and Biodesign mesh affected the early healing response. Resection of 3 cm of intrathoracic esophagus was performed in 10 newly weaned piglets. They were fed through a gastrostomy 8–10 days prior to sacrifice. In order to achieve nonleaking anastomoses, the silicone stent and suturing technique had to be adjusted between the first four and second six piglets. The technical adjustment decreased leakage. A nonleaking anastomosis could not be achieved when the native muscle layers were sewn less central on the bridging graft compared with the mucosa. If there was leakage, the inflammatory response increased, with islets of perivascular T‐lymphocytes and infiltration of macrophages in the native muscle layers. In the bridging area, new vessels were seen in the submucosa in 9 of 10 piglets between 4 and 10 days after surgery. Smooth muscle cells also appeared to move from the cut muscle edges of both the muscularis mucosa and the lamina muscularis and were seen as a layer of several cells under newly formed mucosa. Double staining of the basal membrane of the ingrowing vessels and the pericytes showed that the basal membrane was thinner over some of the pericytes, but there was no accumulation of immature‐looking cells in the submucosa of the bridging area. In this porcine model, where esophageal regrowth was studied by using a bridging graft composed of a silicone stented Biodesign mesh, we can conclude that leakage increased the inflammatory response in early healing. Ingrowth of new vessels was seen in the bridging area and movement of smooth muscle cells was found under newly formed mucosa.